Comparative efficacy of flapped versus flapless dental implant procedures: A meta-analysis - Jain, Preet; Jain, Meetu; Sharma, Chetan; Gaikwad, Rahul N; Porwal, Amit; Barman, Diplina; Talukdar, Rounik; Rai, Nitish (International Journal of Health Sciences, 2024)
Objective: Dental implant procedures are crucial for replacing missing teeth, with various surgical techniques impacting the outcome. This systematic review and meta-analysis aimed to evaluate the effects of flapped and flapless surgical techniques on implant survival and marginal bone loss. Methods: We included clinical studies with at least ten subjects, excluding review articles, editorials, and conference abstracts. Studies were sourced from PubMed, Medline, ERIC, and Wiley, published between 2000 and 2022. Data were analyzed using random effects models to compare implant survival and marginal bone loss between flapped and flapless techniques. Results: The review identified twenty one studies meeting inclusion criteria. Flapless techniques showed a higher implant survival rate with an approximate survival rate of 98.6% in prospective cohort studies and 95.9% in retrospective studies. Marginal bone loss was consistently lower in the flapless group, averaging 0.6 to 2.1 mm, compared to 1.5 to 3 mm in the flapped group. Low-risk studies demonstrated more consistent and reliable results, supporting the efficacy of flapless procedures. Conclusions: Flapless implant surgery offers a viable alternative to traditional flapped surgery, showing higher rates of implant survival and less marginal bone loss. However, successful outcomes depend on advanced imaging, precise surgical techniques, and adequate training. Further high-quality studies are needed to confirm these findings and refine clinical recommendations.